Silver nanoparticles in electrospun ethyl hydroxy ethyl cellulose-PVA Nanofiber: synthesis, characterization and wound dressing applications - Wali, Ashwini; Gorain, Mahadeo; Kundu, Gopal; Badiger, Manohar (Carbohydrate Polymer Technologies and Applications, 2024)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Electrospinning is a simple, cost-effective technique and a reproducible process for both synthetic and <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/natural-polymer" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about natural polymers from ScienceDirect's AI-generated Topic Pages">natural polymers. It is found to be an attractive tool for various applications in biomedical engineering, filtration, protective clothing, catalysis reactions and sensors. Non-ionic cellulose ethers namely Ethyl Hydroxy <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/ethyl-cellulose" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about Ethyl Cellulose from ScienceDirect's AI-generated Topic Pages">Ethyl Cellulose (EHEC) is an important <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/polysaccharide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about polysaccharide from ScienceDirect's AI-generated Topic Pages">polysaccharide which is non-toxic, biocompatible and biodegradable and finds applications as thickening/rheology control agents in paints, cosmetics, detergents, oil recovery and also in the biomedical area. Poly (vinyl alcohol) (PVA) is a semi-crystalline <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/hydrophilic-polymers" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about hydrophilic polymer from ScienceDirect's AI-generated Topic Pages">hydrophilic polymer which is highly biocompatible and non-toxic having good thermal and mechanical properties and also high water solubility. Silver shows powerful antimicrobial activity and is non-toxic. It has been used to cure severe burns and chronic ulcers for many decades and is extensively used as an additive in various fields like prostheses, burn treatment, catheters, vascular grafts, dental resin components, ion exchange fibers, <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/stainless-steel" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about stainless steel from ScienceDirect's AI-generated Topic Pages">stainless steel materials, human skin and coating of <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/medical-device" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about medical devices from ScienceDirect's AI-generated Topic Pages">medical devices. In the present work, EHEC/PVA <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers embedded with silver <a class="topic-link" href="https://www.sciencedirect.com/topics/chemical-engineering/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanoparticles from ScienceDirect's AI-generated Topic Pages">nanoparticles (AgNPs) are studied for their <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/antibacterial-activity" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about antibacterial activity from ScienceDirect's AI-generated Topic Pages">antibacterial activity using both gram positive and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/gram-negative-bacterium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about gram negative bacteria from ScienceDirect's AI-generated Topic Pages">gram negative bacteria. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers show increase in <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/tensile-property" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about tensile properties from ScienceDirect's AI-generated Topic Pages">tensile properties with the addition of silver nano-particles. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/silver-nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about AgNPs from ScienceDirect's AI-generated Topic Pages">AgNPs embedded EHEC/PVA nanofiber mats having 0.5% AgNPs were found to enhance the <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound-healing" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wound healing from ScienceDirect's AI-generated Topic Pages">wound healing with no scar formation in <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wistar-rat" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wistar rats from ScienceDirect's AI-generated Topic Pages">wistar rats. The biological <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vitro<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> and <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vivo<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> studies support the potential of EHEC based <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers as excellent bio-materials for the treatment of severe burns and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wounds from ScienceDirect's AI-generated Topic Pages">wounds. To the best of our knowledge, this is the first report on the electrospinning of EHEC/PVA nanofibers for wound healing applications.